Language In-Form : a Retrospective Exhibition and Catalogue - Berg, Margie; Konsella, Rachel J.; Durocher, Kaleb (My University, 2010)
This project curated and produced a retrospective exhibition and catalog of photographs by Wanrudee Buranakorn. A retrospective exhibition is an exhibition of works produced by an artist over a considerable period, or of an artist's life's work, or of a representative selection of it. The exhibition took place at the Seven Art Gallery, Bangkok, Thailand, July 2010.
Black-and-white poster with text and photograph.
Keywords: Posters; Photography--Exhibitions; Buranakorn, Wanrudee--Exhibitions